Right heart dysfunction in heart failure with preserved ejection fraction - Melenovsky, Vojtech; Hwang, Seok-Jae; Lin, Grace; Redfield, Margaret M; Borlaug, Barry A (European heart journal, 2014)
AIM: Right heart function is not well characterized in patients with heart failure and preserved ejection fraction (HFpEF). The goal of this study was to examine the haemodynamic, clinical, and prognostic correlates of right ventricular dysfunction (RVD) in HFpEF. METHODS AND RESULTS: Heart failure and preserved ejection fraction patients (n = 96) and controls (n = 46) underwent right heart catheterization, echocardiographic assessment, and follow-up. Right and left heart filling pressures, pulmonary artery (PA) pressures, and right-sided chamber dimensions were higher in HFpEF compared with controls, while left ventricular size and EF were similar. Right ventricular dysfunction (defined by RV fractional area change, FAC <35%) was present in 33% of HFpEF patients and was associated with more severe symptoms and greater comorbidity burden. Right ventricular function was impaired in HFpEF compared with controls using both load-dependent (FAC: 40 ± 10 vs. 53 ± 7%, P < 0.0001) and load-independent indices (FAC adjusted to PA pressure, P = 0.003), with enhanced afterload-sensitivity compared with controls (steeper FAC vs. PA pressure relationship). In addition to haemodynamic load, RVD in HFpEF was associated with male sex, atrial fibrillation, coronary disease, and greater ventricular interdependence. Over a median follow-up of 529 days (IQR: 143-1066), 31% of HFpEF patients died. In Cox analysis, RVD was the strongest predictor of death (HR: 2.4, 95% CI: 1.6-2.6; P < 0.0001). CONCLUSION: Right heart dysfunction is common in HFpEF and is caused by both RV contractile impairment and afterload mismatch from pulmonary hypertension. Right ventricular dysfunction in HFpEF develops with increasing PA pressures, atrial fibrillation, male sex, and left ventricular dysfunction, and may represent a novel therapeutic target.
Keywords: Stroke Volume; Kaplan-Meier Estimate; Ventricular Dysfunction, Right; Female; Pulmonary hypertension; Atrial Fibrillation; ženské pohlaví; Kaplanův-Meierův odhad; Heart Failure; Hemodynamics; hemodynamika; lidé; srdeční selhání; studie případů a kontrol; prognóza; Gender; Sex Factors; retrospektivní studie; Male; Case-Control Studies; Aged; sexuální faktory; Ventricular function; tepový objem; dysfunkce pravé srdeční komory; Heart failure; Prognosis; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Haemodynamics; Retrospective Studies; Middle Aged; Atrial fibrillation; Humans